Learn Adobe Animate CC for interactive media Adobe certified associate exam preparation - Labrecque, Joseph; Schwartz, Rob 1969- (Adobe Press, 2016)
"Knowing the industry-standard animation and interactivity tool Adobe Animate CC (previously known as "Flash Professional") can help you get a foothold in the exciting web design and mobile app-development world. Learn Animate CC by building cool creative projects that will teach you how to: Design and animate vector artwork -- Compose an animated greeting card using HTML5 -- Build a promotional video with text and images animated in 3D -- Construct a working digital clock using ActionScript -- Design and code an interactive quiz for mobile devices."--Publisher
Place of publication from publisher's Web site. - Includes index. - Includes glossary and index. - Online resource; title from title page (Safari, viewed April 19, 2016)
Keywords: Flash (Computer file) -- Study guides -- Examinations; Computer animation -- Examinations; Web site development -- Computer programs; Web sites -- Authoring programs; Flash (Computer file); Animation par ordinateur; Examens; Sites Web; Systèmes-auteur; ART; Film & Video; PHOTOGRAPHY; Techniques; Cinematography & Videography; Computer animation; Web site development; Computer programs; examination study guides; Examinations; Study guides; Guides de l'étudiant